Catalytic Site Cooperativity in Dimeric Methylthioadenosine Nucleosidase - Wang, Shanzhi (American Chemical Society, 2014)
[Image: see text] 5′-Methylthioadenosine/S-adenosylhomocysteine nucleosidases (MTANs) are bacterial enzymes that catalyze hydrolysis of the N-ribosidic bonds of 5′-methylthioadenosine (MTA) and S-adenosylhomocysteine (SAH) to form adenine and 5-thioribosyl groups. MTANs are involved in AI-1 and AI-2 bacterial quorum sensing and the unusual futalosine-based menaquinone synthetic pathway in Streptomyces,Helicobacter, and Campylobacter species. Crystal structures show MTANs to be homodimers with two catalytic sites near the dimer interface. Here, we explore the cooperative ligand interactions in the homodimer of Staphylococcus aureus MTAN (SaMTAN). Kinetic analysis indicated negative catalytic cooperativity. Titration of SaMTAN with the transition-state analogue MT-DADMe-ImmA gave unequal catalytic site binding, consistent with negative binding cooperativity. Thermodynamics of MT-DADMe-ImmA binding also gave negative cooperativity, where the first site had different enthalpic and entropic properties than the second site. Cysteine reactivity in a single-cysteine catalytic site loop construct of SaMTAN is reactive in native enzyme, less reactive when inhibitor is bound to one subunit, and nonreactive upon saturation with inhibitor. A fusion peptide heterodimer construct with one inactive subunit (E173Q) and one native subunit gave 25% of native SaMTAN activity, similar to native SaMTAN with MT-DADMe-ImmA at one catalytic site. Pre-steady-state kinetics showed fast chemistry at one catalytic site, consistent with slow adenine release before catalysis occurs at the second catalytic site. The results support the two catalytic sites acting sequentially, with negative cooperativity and product release being linked to motion of a catalytic site loop contributed by the neighboring subunit.